Natural Resources Management in Ghana: The role of the Decentralised Government - Gumah, Agolko Isaac (CGIAR Challenge Program on Water and Food, 2013)
Ghana is endowed with a lot of natural resources but these resources are depleting at rates that are worrisome. If care is not taken the environment will lose all these gifts of nature. However, most Ghanaians livelihoods are linked to these natural resources. The management of these natural resources are carried by various stakeholders. The role of the decentralised government in managing these natural resources and the way they collaborate in doing it has not been deeply researched in to by researchers.